Comparative analysis of hemodynamic characteristics of the biological xenogenic pericardial prosthesis MEDINGE-BIO with “easy change” system and the xenogenic aortic prosthesis Hancock II after aortic valve replacement - K. A. Petlin; E. A. Kosovskikh; E. V. Lelik; B. N. Kozlov (Российский кардиологический журнал)
Aim. To compare the outcomes of aortic valve replacement using the xenogenic aortic prosthesis Hancock II and the novel Russian xenogenic pericardial prosthesis MEDINGE-BIO.Material and methods. The study included patients operated on for aortic stenosis in the cardiac surgery department № 1 of the Cardiology Research Institute (Tomsk National Research Medical Center). All patients were divided into two groups. The first group included 54 patients with Hancock II prostheses, the second — 91 patients with MEDINGE-BIO prostheses. Hemodynamic characteristics of heart valves were assessed by echocardiography before surgery and before discharge (on average 10 days after surgery).Results. When comparing hemodynamic parameters before and after surgery, significant differences between the groups were not obtained. The average pressure gradient after surgery using Hancock II and MEDINGE-BIO prosthesis was 21,6±7,9 and 17,9±5,6 mm Hg, respectively (p=0,05).Conclusion. The comparative analysis showed that the novel biological prosthesis MEDINGE-BIO has comparable hemodynamic characteristics with the well-known aortic prosthesis Hancock II.